2015
DOI: 10.14453/aabfj.v9i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Red Queen Takes White Knight: The Commercialisation of Accounting Education in Australia

Abstract: This paper investigates the adaptive and maladaptive consequences of changes resulting from the commercialisation of Australian universities, specifically their accounting schools, and aims to identify the organisational changes triggered by competition that affect the growth of universities over time. The paper synthesises organisational learning theory, benchmarking theory, mimetic isomorphism and institutional theories, which are presented as "the Red Queen", itself an evolutionary theory; this synthesis pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Numerous studies undertaken in developed countries such Australia, New Zealand, the USA and the UK strongly stressed that universities continue to place accounting graduates in career dilemmas (Gribbin and Saini, 2016; Lawson et al , 2014; Kushniroff, 2012; Botes, 2009; Jackling and De Lange, 2009; Kavanagh and Drennan, 2008; De Lange et al , 2006). In Australia, it has been observed that there is an increase in accounting graduates driven by international students; however, it is experiencing shortage of practicing accountants because graduates are inadequately prepared (Watts et al , 2015; McDowall and Jackling, 2010). Similarly, Evans et al (2010, p. 14) pointed out that:…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies undertaken in developed countries such Australia, New Zealand, the USA and the UK strongly stressed that universities continue to place accounting graduates in career dilemmas (Gribbin and Saini, 2016; Lawson et al , 2014; Kushniroff, 2012; Botes, 2009; Jackling and De Lange, 2009; Kavanagh and Drennan, 2008; De Lange et al , 2006). In Australia, it has been observed that there is an increase in accounting graduates driven by international students; however, it is experiencing shortage of practicing accountants because graduates are inadequately prepared (Watts et al , 2015; McDowall and Jackling, 2010). Similarly, Evans et al (2010, p. 14) pointed out that:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bui and Porter (2010, p. 45) classified these constraints as institutional factors and their findings identified additional “institutional factors which includes entry criteria (imposed by the University) that permit students with insufficient ability to enrol in the accounting programme and the university’s tenure and promotion policies which motivate educators to devote time and effort to research rather than teaching activities”. Institutional factors inhibit academics’ credence to focus on teaching excellence (Watts et al , 2015; Merino, 2006). Furthermore, there are student-related constraints, specifically, students’ ability and aptitude.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Clarity of goals, the ability to select undistorted performance metrics and the degree to which managers know and control the transformation process tends to enhance performance (Speklé & Verbeeten, 2014). A few tools have been suggested such as www.hrmars.com Performance Alignment Matrix (Melnyk, Bititci, Platts, Tobias, & Andersen, 2014), the Performance Wheel and Small Business Performance Pyramid (Watts, McNair, & Bard, 2010).…”
Section: Introductionmentioning
confidence: 99%